The Caregiver Health Effects of Caring for Young Children with Developmental Disabilities: A Meta-analysis - Masefield, Sarah C.; Prady, Stephanie L.; Sheldon, Trevor A.; Small, Neil; Jarvis, Stuart; Pickett, Kate E. (Maternal and child health journal, 2020)
Objectives Mothers of school age and older children with developmental disabilities experience poorer health than mothers of typically developing children. This review assesses the evidence for the effect on mothers’ health of caring for young children with developmental disabilities, and the influence of different disability diagnoses and socioeconomic status. Methods Medline, EMBASE, PsycINFO and CINAHL were searched. Studies measuring at least one symptom, using a quantitative scale, in mothers of preschool children (0–5 years) with and without a diagnosed developmental disability were selected. Random effects meta-analysis was performed, and predictive intervals reported due to high expected heterogeneity. Results The meta-analysis included 23 estimates of association from 14 retrospective studies for the outcomes of stress (n = 11), depressive symptoms (n = 9), general health (n = 2) and fatigue (n = 1). Caring for a child with a developmental disability was associated with greater ill health (standardised mean difference 0.87; 95% predictive interval − 0.47, 2.22). The largest association was for mixed developmental disabilities (1.36; − 0.64, 3.36) and smallest for Down syndrome (0.38; − 2.17, 2.92). There was insufficient socioeconomic information to perform subgroup analysis. The small number of studies and data heterogeneity limited the precision of the estimates of association and generalizability of the findings. Conclusions for Practice Mothers of young children with developmental disabilities may have poorer health than those with typically developing children. Research is needed to identify whether the relationship is causal and, if so, interventions that could reduce the negative effect of caregiving.